Monitoring High-Risk Sex Offenders with GPS Technology in California, 2006-2009 - Gies, Stephen ([Verlag nicht ermittelbar], 2016)
These data are part of NACJD's Fast Track Release and are distributed as they were received from the data depositor. The files have been zipped for NACJD release, but not checked or processed except for the removal of direct identifiers. Users should refer to the accompanying readme file for a brief description of the files available with this collection and consult the investigator(s) if further information is needed. The purpose of the evaluation was to determine the effectiveness of global positioning system (GPS) monitoring of high-risk sex offenders (HRSOs) who were placed on parole in California between 2006 and 2009. This study integrates both outcome and process evaluation components to assess the impact of the California Department of Corrections and Rehabilitation (CDCR) GPS supervision program by employing a nonequivalent-group quasi-experimental design with a multilevel survival model. The outcome of interest was recidivism. A propensity score matching procedure was used to account for the differences between the treatment and comparison groups. Parolee data were collected from six sources: the California Department of Corrections and Rehabilitation (CDCR) data management system, official arrest records, parole supervision records, GPS monitoring data, CDCR cost information, and a CDCR parole agent survey. The final sample included 516 parolees equally divided between the treatment and control groups and 153 GPS parole agents with HRSO caseloads.